2012
DOI: 10.1093/bja/aes242
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and patterns of infections in patients with underlying haematological malignancies admitted to intensive care

Abstract: are recommended when neuraxial techniques are planned. Ultrasound-assisted spinal anaesthesia may be helpful with challenging spinal anatomy but is not always successful and real-time ultrasound-guided spinal anaesthesia may be necessary. 8 However, an experienced practitioner in ultrasound-guided spinal techniques may be required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
3
0
0
Order By: Relevance
“…Although the survival of cancer patients with septic shock has previously been reported to not be too dissimilar from mixed populations with septic shock [11], an increased prevalence of septic shock would be expected to translate into increased mortality. Our findings are similar to published data on non-CAP critically ill patients with cancer that also show an increased incidence of septic shock [1214].…”
Section: Discussionsupporting
confidence: 92%
“…Although the survival of cancer patients with septic shock has previously been reported to not be too dissimilar from mixed populations with septic shock [11], an increased prevalence of septic shock would be expected to translate into increased mortality. Our findings are similar to published data on non-CAP critically ill patients with cancer that also show an increased incidence of septic shock [1214].…”
Section: Discussionsupporting
confidence: 92%
“…Results from blood cultures are not often included in ICU cohort studies. In a small cohort study of critically ill patients with a haematologic malignancy, no association was found between infection‐related characteristics and mortality , which is in line with our observations. Another study found that in patients with a haematological malignancy and nosocomial Gram‐negative bacteraemia, aplastic anaemia was a risk factor for early (7‐day) mortality .…”
Section: Discussionsupporting
confidence: 91%
“…This underlines the current perception that patients with a haematological malignancy have a comparable prognosis to other critically ill non‐cancer patients with comparable disease severity. Moreover, the 28‐day mortality of 38% in our cohort is comparable with previous reports in critically ill patients with haematological malignancy and underlines that survival is improving in these patients .…”
Section: Discussionsupporting
confidence: 89%